Is Team Sport the Key to Getting Everybody Active, Every Day? A Systematic Review of Physical Activity Interventions Aimed at Increasing Girls' Participation in Team Sport - Rosalie Allison; Emma L. Bird; Stuart McClean (AIMS Press, 2017)
Background: It is estimated that 21% of boys and 16% of girls in England meet recommended physical activity guidelines. Team sport has the potential to increase physical activity levels; however, studies show that gender-based factors can influence girls' participation in team sport. Furthermore, evidence for the effectiveness of interventions promoting team sport among girls is limited. This systematic review aimed to assess the impact of physical activity interventions on secondary school-aged girls' (aged 11-18 years) participation in team sport and to identify potential strategies for increasing participation. Methods: Electronic databases and grey literature were systematically searched for studies of interventions targeting team sport participation among girls in the UK. Results were exported to Refworks, duplicates removed and eligible studies identified. Extracted data included: participant details, such as sample size and age; components of the intervention; outcomes assessed; and each study was quality appraised. Due to heterogeneity across studies, results were presented narratively. Results: Four studies sourced from the grey literature met the inclusion criteria. Findings suggest that physical activity interventions can encourage girls to try new sports, but evidence is limited in relation to sustained participation. Potential strategies for promoting participation included: consultation with girls, implementation of appropriate peer-leaders and friendship group strategies, early intervention and consideration of intervention setting. Conclusions: This review highlights the limited availability of evidence on the effectiveness of physical activity interventions for promoting team sport participation among girls in the UK. Findings indicate that future research is needed to improve the methodological quality of complex intervention evaluation. Physical activity interventions may have the potential to encourage girls to try team sport, but their impact on sustained participation, and subsequent physical activity outcomes, is less apparent.